Karakteristik kewarganegaraan yang demokratis dalam perspektif demokrasi Pancasila - Cholisin, Cholisin (Jurnal Civics: Media Kajian Kewarganegaraan, 2007)
Pancasila democracy is a constitutional democracy. Characteristics of Pancasila democracy are: (1) the scope is not limited in the sense of political democracy, but also covering the economic and social democracy, (2) in the spirit it contains the religious, humanist, collectivism (kekelurgaanpatterns of village life), (3) although modern democratic institutions that are used but in decisionmaking mechanisms of soao-cultural institution that is native consultation system. Pancasila democracy has these' characteristics, a characteristic of democratic citizen in the Homeland, for . example: relegious, humanist, nationalist, democratic and socialjustice. Suchh characteristics will distinguish the state with citizens of non-Pancasila democracy